2008
DOI: 10.1111/j.1750-2659.2008.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for avian influenza A infections among Iowa’s agricultural workers

Abstract: Background  Identifying risk factors for zoonotic influenza transmission may aid public health officials in pandemic influenza planning. Objectives  We sought to evaluate rural Iowan agriculture workers exposed to poultry for previous evidence of avian influenza virus infection. Methods  In 2004, we enrolled 803 rural adult Iowans in a 2‐year prospective study of zoonotic influenza transmission. Their enrollment data and sera were compared with those of 66 adult controls enrolled at the University of Iowa in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 28 publications
6
57
0
Order By: Relevance
“…Third, because there were no reliable or referenced cut-off values of seropositivity for different subtypes in previous studies, cut-off values of seropositivity were set at an HI titre of 40 for H6N1, H7N3 and H7N9 subtypes and at 1:80 for H5N2. In conclusion, this study indicates that poultry workers have a higher risk of exposure to AIVs during occupational activities and consistently supports the results reported previously by other studies [10,[21][22][23][24]. Therefore, active surveillance for the early detection and intervention of viral infections in live poultry should be conducted continuously.…”
Section: Discussionsupporting
confidence: 92%
“…Third, because there were no reliable or referenced cut-off values of seropositivity for different subtypes in previous studies, cut-off values of seropositivity were set at an HI titre of 40 for H6N1, H7N3 and H7N9 subtypes and at 1:80 for H5N2. In conclusion, this study indicates that poultry workers have a higher risk of exposure to AIVs during occupational activities and consistently supports the results reported previously by other studies [10,[21][22][23][24]. Therefore, active surveillance for the early detection and intervention of viral infections in live poultry should be conducted continuously.…”
Section: Discussionsupporting
confidence: 92%
“…Among these birds, those living in wetland and aquatic environments (e.g., Anseriformes spp., particularly ducks, geese, and swans, and Charadriiformes spp., particularly gulls, terns, and waders) are by far the major source of these isolates and are generally accepted as major natural IAV reservoirs (25, 50). Infected wild birds, especially migratory waterfowl, are believed to serve as a vector facilitating the spread of avian IAVs among wild bird species and different geographic locations, and are one source for viral transmission into domestic poultry (34, 50), swine (19), and humans (16). …”
Section: Introductionmentioning
confidence: 99%
“…Gray et al also found neutralising antibodies to H6N2 and H7N2 influenza virus in the same study, but the prevalences were not significantly different between the exposed group and non-exposed controls (1.4 vs 4.0% and 5.5 vs 0%) [63]. Five other studies failed to find serological evidence of H6 or H7 exposure [18,63,80,102,117]. Only one-cross sectional study looked at H7N9 exposure, finding a seroprevalence of 6.3% in poultry workers in Guangdong, China, and a significantly lower percentage in non-exposed controls (0%) [110].…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, two studies executed in Romania and Vietnam found no antibodies in either group [18,91]. Gray et al also found neutralising antibodies to H6N2 and H7N2 influenza virus in the same study, but the prevalences were not significantly different between the exposed group and non-exposed controls (1.4 vs 4.0% and 5.5 vs 0%) [63]. Five other studies failed to find serological evidence of H6 or H7 exposure [18,63,80,102,117].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation